Overview on the management of adult urinary incontinence. Issue 4 (April 2020) - Yang, Bob; Foley, Steve
Abstract: Urinary incontinence is a common presentation and can manifest either as stress, urge or mixed incontinence. Though primarily a condition affecting women, the increasing uptake of prostate surgery for benign disease and cancer, whereupon up to one in five patients end up experiencing stress incontinence, means the prevalence of incontinence in men is increasing. A thorough assessment is necessary to identify the underlying urological abnormality and to guide appropriate management. Conservative approaches consist of treating constipation, the use of containment devices, weight loss, bladder training and pelvic floor muscle training. Medical management frequently consists of the use of antimuscarinics and newer agents such as mirabegron. Surgical management is considered if previous therapies fail. Urodynamic assessment and subsequent multidisciplinary team review is commonly undertaken prior to invasive therapy. Surgical options include slings, bulking agents, botulinum toxin A, neuromodulation, artificial urinary sphincter, augmentation cystoplasty and urinary diversion. To note, the recent controversies with mesh has meant a sharp drop off in their use and higher uptake of autologous options. All these options are discussed in this article, including indications, outcomes and side-effects. For all patients, a stepwise approach is recommended, beginning with the least invasive options before moving onto more complex surgery with higher risk of severe complications. Patients with refractory urinary incontinence should be considered for entry into clinical trials where novel therapies are being assessed.